Single-Center Experience with Therapeutic Hypothermia for Hypoxic–Ischemic Encephalopathy in Infants with <36 Weeks' Gestation - Moran, Patricia; Sullivan, Kelsey; Zanelli, Santina A.; Burnsed, Jennifer (American Journal of Perinatology, 2024)
Objective Hypoxic–ischemic encephalopathy (HIE) is a leading cause of morbidity and mortality in neonates. Therapeutic hypothermia (TH) has improved outcomes and mortality in infants with >36 weeks' gestational age (GA) with moderate-to-severe HIE. There are limited data on the safety and efficacy of TH in preterm infants with HIE. This study describes our experience and examines the safety of TH in neonates with <36 weeks' GA.Study Design A single-center, retrospective study of preterm neonates born at <36 weeks' GA with moderate-to-severe HIE and treated with TH, compared to a cohort of term neonates with HIE (≥37 weeks' GA), was conducted. The term cohort was matched for degree of background abnormality on electroencephalogram, sex, inborn versus outborn status, and birth year. Medical records were reviewed for pregnancy and delivery complications, need for transfusion, sedation and antiseizure medications, electroencephalography and imaging findings, and in-hospital mortality.Results Forty-two neonates born at <36 weeks' GA with HIE received TH between 2005 and 2022. Data from 42 term neonates were analyzed for comparison. The average GA of the preterm cohort was 34.6 weeks and 39.3 weeks for the term cohort. Apgar scores, degree of acidosis, and need for blood product transfusions were similar between groups. Preterm infants were more likely to require inotropic support (55 vs. 29%, p = 0.026) and hydrocortisone (36 vs. 12%, p = 0.019) for hypotension. The proportion of infants without evidence of injury on magnetic resonance imaging was similar in both groups: 43 versus 50% in preterm and term infants, respectively. No significant difference was found in mortality between groups.Conclusion In this single-center cohort, TH in preterm infants appears to be as safe as in term infants, with no significant increase in intracranial bleeds or mortality. Preterm infants more frequently required inotropes and steroids for hypotension. Further research is needed to determine efficacy of TH in preterm infants.Key Points
Keywords: preterm infants; hypoxic–ischemic encephalopathy; therapeutic hypothermia; cooling